How to Improve the Quality of Learning for Early Childhood? An Implementation of Education Management in the Industrial Revolution Era 4.0 - Sri Supiah Cahyati; Tukiyo Tukiyo; Nanda Saputra; Julyanthry Julyanthry; Herman Herman (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to analyze the planning, implementation, and supervision of learning in the 4.0 industrial revolution era at one kindergarten school located in Pematangsiantar since early childhood education is expected to produce creative, character, competent and innovative graduates which can only be done through the creation of conducive learning conditions supported by learning management. The research method used is a qualitative approach with descriptive research. The research was carried out at one kindergarten school located in Pematangsiantar with data collection techniques through interviews and observations. The results showed that based on existing competencies in the 4.0 industrial revolution era, there were innovations and a number of breakthroughs produced by teachers in improving the quality of learning in the form of curriculum development and the use of information and communication technology in carrying out several approaches and learning strategies. One of the breakthroughs that has been made is video learning for early childhood. All processes of innovation and breakthroughs in the learning process are supported by the ability of teachers to implement good learning management principles.